Effect of ethanolic extract of Chromolaena odorata on the kidneys and intestines of healthy albino rats - Stanley Anyanwu; Imeobong J. Inyang; Enosakhare A. Asemota; Okechi O. Obioma; Dorathy C. Okpokam; Victoria O. Agu (Integrative Medicine Research, 2017)
Background: The use of plants and plant products for medicinal purposes is an age-long practice in traditional communities and is becoming prominent globally. This study was performed to evaluate the effect of ethanolic extract of Chromolaena odorata on the kidney and intestine of albino rats. Methods: Twenty growing albino rats with an average weight of 54 g were used in this study. They were grouped into four groups. Groups 1, 2, and 3, known as the test groups, were given 50 mg/kg, 100 mg/kg, and 250 mg/kg ethanolic extract of C. odorata, respectively, while the control group was given distilled water orally. The experiment was performed for 6 weeks. The animals were killed using chloroform suffocation. The kidneys and the intestine were harvested and fixed in 10% neutral buffered formalin for histological analysis. Blood samples were collected from the animals by heart puncture for estimation of creatinine and urea levels. Results: The creatinine, urea, aspartate aminotransferase, alanine transaminase, and alkaline phosphatase levels of blood sample from the test group were significantly different when compared with the control (p < 0.05). The histological sections of the kidneys in this study showed no signs of degeneration. Infiltration of inflammatory cells and epithelial erosion were observed in the histology sections of the intestine of all the test groups. Conclusion: The results from this study revealed that uncontrolled use of this plant extract has an adverse effect on the kidney function and on the histology of the intestine of the rats used in this study.